Planning & Controlling Tourism Landscape Design Project using Critical Chain Project Management (CCPM) Schedulling - Alivia Rosy Walidonna; Iwan Vanany (Institut Teknologi Sepuluh Nopember, 2020)
Project Management must meet the performance criteria of timeliness and budget control agreed between the project owner, contractor and supervisor. However, the level of uncertainty in the project implementation process is very high and causes delays and over budgeting. The Village Nongkojajar is a Proposed Integrated Agropark Project as a result of the revitalization of the non-productive land of the Horticultural Seed Farm owned by the Government of East Java Province. The Landscape Architecture Project has a Creative Value Chain which is divided into Creation - Implementation - Management. Therefore scheduling and controlling the project becomes important in order to to estimate working time and the project remains in accordance with the predetermined project timeline and whenever corrective action is needed. The relevance of Project Management in this research is that with high project problems, require a good planning process. The Project can be completed quickly than the specified time and more cost effective. Critical Chain Project Management (CCPM) is one method for completing and preparing projects that focus on the resource requirements for implementing projects by adding project buffers, feeding buffers and resource buffers. By analyzing using CCPM, researchers can look for optimization and control in implementing project scheduling.